Triangle angle sums related to translation curves in Sol geometry - SZIRMAI, Jenő (Studia Universitatis Babeș-Bolyai Mathematica, 2022)
After having investigated the geodesic and translation triangles and their angle sums in Nil and S—L2R geometries we consider the analogous problem in Sol space that is one of the eight 3-dimensional Thurston geometries. We analyse the interior angle sums of translation triangles in Sol geometry and prove that it can be larger or equal than π. In our work we will use the projective model of Sol described by E. Molnar in [9]. Mathematics Subject Classification (2010): 53A20, 53A35, 52C35, 53B20. Received 13 August 2020; Accepted 16 August 2020.